Management of Decongestion in Acute Heart Failure: Time for a New Approach? - Pramudyo, Miftah; Putra, Iwan Cahyo Santosa; Zulkarnain, Edrian; Danny, Siska Suridanda; Bagaswoto, Hendry Purnasidha; Anjarwani, Setyasih; Mazwar, Irmaliyas; Juzar, Dafsah Arifa; Pratama, Vireza; Habib, Faisal; Ispar, Akhtar Fajar Muzakkir Ali; Widyantoro, Bambang (Jurnal Kardiologi Indonesia, 2022)
As the primary cause of hospitalization in acute heart failure (AHF) patients, congestion was responsible for a higher risk of mortality, rehospitalization, and renal dysfunction in AHF patients. Although loop diuretic was routinely used as the mainstay of AHF therapy, it is still ineffective to obtain the euvolemic state in most hospitalized AHF patients. Therefore, a higher loop diuretic dose was often required to increase the decongestion effect. However, consequently, it can cause several detrimental complications, including renal dysfunction, neurohormonal activation, hyponatremia, hypokalaemia, and reduced blood pressure, which eventually result in poor prognosis. Hence, the new approach may be proposed to optimize decongestion in acute phase, including the use of arginine vasopressin V2 receptor antagonist – Tolvaptan. As an additive therapy to loop diuretic in AHF patients, it can be considered due to its several beneficial effects, including greater decongestion effect, lowered worsening renal function incidence, counteract neurohormonal activation, neutralized hyponatraemic state, no alteration of potassium metabolism, stabilize the blood pressure, and reduced requirement of a higher dose of loop diuretic to achieve an equal or even greater decongestion effect compared to a high dose of loop diuretic alone. Tolvaptan provided favourable outcomes in several specific populations and was considered safe with several mild adverse effects. Several guidelines across countries have approved the use of Tolvaptan in AHF patients with or without hyponatremia. The initial dose of Tolvaptan was 7.5 to 15 mg and can be titrated up to 30 mg. However, further studies were still required to determine the timing dose and optimal dose of Tolvaptan in general and elderly populations with AHF, respectively.This article has a related Erratum.